2012
DOI: 10.1007/s13669-012-0020-9
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Diabetes: Seeing Both the Forest and the Trees

Abstract: Gestational diabetes is a heterogeneous disorder. Various metabolic etiologies underpin the diagnosis and influence perinatal outcomes as well as an individual's propensity for the subsequent development of diabetes. Recent landmark studies have driven a review of the diagnostic criteria for gestational diabetes, with an emergent category, "overt diabetes during pregnancy," recognizing the increased surveillance required for some women. As we strive for consensus in diagnosis at a global level, consideration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…However, they obscure the heterogeneity in risk factors, clinical phenotype, treatment response, and outcomes seen in women presenting with GDM. [8][9][10][11][12][13] The risk of an adverse pregnancy outcome is clearly related to elevated blood glucose levels in GDM. 1 However, the relationship is complex, and an individual's risk is modified by interrelated factors, including maternal weight, 14,15 gestational weight gain, 16 ethnicity, 17 and genotype.…”
Section: Gestational Diabetes Is a Highly Heterogeneous Conditionmentioning
confidence: 99%
“…However, they obscure the heterogeneity in risk factors, clinical phenotype, treatment response, and outcomes seen in women presenting with GDM. [8][9][10][11][12][13] The risk of an adverse pregnancy outcome is clearly related to elevated blood glucose levels in GDM. 1 However, the relationship is complex, and an individual's risk is modified by interrelated factors, including maternal weight, 14,15 gestational weight gain, 16 ethnicity, 17 and genotype.…”
Section: Gestational Diabetes Is a Highly Heterogeneous Conditionmentioning
confidence: 99%
“…The need for refined and targeted approaches is strengthened by the heterogeneous population defined by current diagnostic criteria for GDM. 10 Pregnancy risk is clearly related to elevated glucose in GDM, but the relationship is complex, and an individual’s risks are modified by interrelated factors including maternal weight, 11 12 gestational weight gain, 13 ethnicity 14 and genotype. 15 For example, it has recently been shown that within the two largest maternity services in Australia, ethnic Chinese women with GDM had a lower risk of large-for-gestational-age (LGA) babies and neonatal hypoglycaemia compared with Caucasian women, even adjusting for confounders.…”
Section: Introductionmentioning
confidence: 99%